Conversations on leadership : wisdom from global management gurus. - Liu, Lan (Jossey-Bass, 2010)
A veritable who's who in leadership, Conversations on Leadership features Warren Bennis, Jim Kouzes, John Kotter, Noel Tichy, Peter Senge, James March, Howard Gardner, Bill George, and others. Since each leader has a distinctive approach, this book provides the multi-faceted truths of leadership to broaden and deepen the understanding of the readers.